Psychosexual fixation and sexual deviance: The impact of parental abandonment in Haruki Murakami's Kafka on the Shore - Zuhrul Anam; Amara Zulfa Claudia Izzak (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
The development of psychosexual stages in children significantly influences their behavior. There are five stages: oral, anal, phallic, latent, and genital. Disruptions or fixations during any stage can impact societal conduct and relationships. In Kafka on the Shore, parental abandonment causes fixation in one of these stages, as seen in the main character, Kafka Tamura. This disrupted bond leads to repressed emotions and unfulfilled desires manifesting as sexual deviance. Therefore, this study aims to describe the development of sexual deviance due to traumatic parental abandonment in Haruki Murakami’s Kafka on the Shore, using a descriptive qualitative method and analyzed through Sigmund Freud’s psychoanalytic theory. It affirms that neglectful parental figures can significantly impact a child's psychological development.